Results of a production analysis survey of cow herds in Kansas - D. Simms; Michael R. Langemeier; S. Utter; G. Fike; C. Bandyk (Kansas Agricultural Experiment Station Research Reports, 1993)
A survey of production levels and management practices of 205 cow herds representing over 26,000 cows in Kansas was conducted in 1991. These operations were located throughout Kansas except for the Northwest corner. Emphasis was placed on determining levels of production and reproductive parameters. Breeders emphasized calf crop. For example, the average calf crop was 91.6%, with 4.3% open females and 4.4% calf death loss. Cumulative calving percentages by 21-day calving periods were 32, 55, and 68%. Average weaning weights were 550 lb. for steers and 515 lb for heifers. Additionally, information was collected on breeding, nutrition, health, and general management practices.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Cow/calf; Production; Reproduction; Management; Survey